2013
DOI: 10.1002/hep.26253
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mammalian target of rapamycin complex 1 (mTORC1) and Raf/Pyk2 by growth factor-mediated Eph receptor 2 (EphA2) is required for cholangiocarcinoma growth and metastasis

Abstract: Eph receptor 2 (EphA2) overexpression is frequently accompanied by the loss of its cognate ligand during tumor progression. However, the molecular mechanism of this ligandindependent promotion of tumor by EphA2 remains unclear in highly malignant and fatal cholangiocarcinoma (CC). We examined the biological role of EphA2 in tumor growth and metastasis in CC tissues and cells according to the degree of differentiation and we explored the downstream signaling pathways of EphA2. Growth factor-mediated EphA2 overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 64 publications
(42 reference statements)
7
28
0
Order By: Relevance
“…Inhibition of mTOR has been demonstrated to suppress liver tumor growth and metastasis (9,10). Several clinical and preclinical studies have demonstrated that the mTOR inhibitor rapamycin and its analogues can be used to treat various types of solid tumor, including esophageal squamous cell carcinoma (11), lung cancer (12), renal cell carcinoma (13) and prostate cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of mTOR has been demonstrated to suppress liver tumor growth and metastasis (9,10). Several clinical and preclinical studies have demonstrated that the mTOR inhibitor rapamycin and its analogues can be used to treat various types of solid tumor, including esophageal squamous cell carcinoma (11), lung cancer (12), renal cell carcinoma (13) and prostate cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Two prominent oncogenic pathways, FAK and AKT, have been associated with EphA2 overexpression (30,(44)(45)(46). FAK pathway has been reported to be inversely correlated with miR-200a expression in ovarian tumors, the seed sequence of which is the same as that of the miR-141 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Among Eph receptors, EphA2 and EphB2 were increased in CCA tumors and correlated with the metastatic status of patients and poorer tumor differentiation [91,92].…”
Section: Receptor Tyrosine Kinases (Figure 2b)mentioning
confidence: 99%
“…Eph Receptors and their ligands are expressed at very low levels in normal cholangiocytes [91,92]. Among Eph receptors, EphA2 and EphB2 were increased in CCA tumors and correlated with the metastatic status of patients and poorer tumor differentiation [91,92].…”
Section: Receptor Tyrosine Kinases (Figure 2b)mentioning
confidence: 99%